The Correlation Between Mastery of Vocabulary and Reading Comprehension Students: Case Study SMP Swasta Tenera PTPN IV Kab. Langkat - Amos Sider Tamboy (Institute of Computer Science (IOCS), 2020)
This research deals with the student’s mastery of vocabulary and reading comprehension. It is aimed at finding out whether there is a high correlation between the mastery of vocabulary and reading comprehension. In this research the population was taken students of SMP Swasta Tenera PTPN IV Kab. Langkat. The total number of the samples was 20 students. After the data had been collected, the writer analyzed the data by using the formula of Pearson Product Moment. After calculating the correlation of mastery vocabulary and reading comprehension test, it was obtained that the correlation coefficient was 0,57. It means that there is a high correlation between mastery of vocabulary and reading comprehension. It implies that the higher the student’s mastery on vocabulary, the better they can comprehend the reading texts.